PUBLIC POLICY EXCEPTION AS GROUND FOR EXCLUDING THE RECOGNITION AND ENFORCEMENT OF ARBITRATION AWARD IN THE LEGAL SYSTEM OF THE REPUBLIC OF ARMENIA - Yeremyan, Lilit; Simonyan, Taron (State and Law, 2022)
Public policy exception, which is ground for excluding the recognition and enforcement of arbitration award is considered means of state judicial control and element of judicial sovereignty of the state. There is no precise definition of the concept of “public policy” and precise legal content of the public policy exception, however, these issues are subject to wide discussions on practical level and in the legal doctrine. Public policy exception is often interpreted as contradiction with the domestic public policy, which includes but is not limited to general principles of law (domestic public policy). In the framework of cases on recognition and enforcement of arbitration awards the courts of the Republic of Armenia are obliged to check ex officio if the enforcement of arbitral award would violate the public policy of the Republic of Armenia, as well as to refuse the recognition and enforcement of the arbitration award in case of such violation. And according to the approach undertaken by the Republic of Armenia public policy is considered domestic public policy, the legal content of which is still to be defined by the courts of the Republic of Armenia on case by case basis taking into account all circumstances of the given case.
Keywords: 1958 New York Convention; recognition and enforcement of arbitration award; public policy; public policy exception; judicial control